Revisiting the past to understand the present and future of soil health in Brazil - Silva, Antonio Marcos Miranda; Araújo, Victor Lucas Vieira Prudêncio de; Cardoso, Elke Jurandy Bran Nogueira (Frontiers in Soil Science, 2023)
As Soil Scientists, we are gathering important and valuable knowledge about the chemical, physical and biological processes in soil, and with the increasing effects of climate change, this knowledge may play a pivotal role in the future of our planet. However, we must revisit our past to understand how humanity's evolution has shaped the current state of soil health. Furthermore, we must also bear in mind that we are funded and supported by the society in which we live, and therefore social and political factors will inevitably play a part in the future of soil health. In this review, we address important historical aspects of crop development, soil microbiomes and fauna, combined with the provision of key ecosystem services to ensure soil sustainability. In addition, we provide a brief overview of soil health in Brazilian biomes and the risks of forest extinction in the Anthropocene Epoch, linking its ecological role in the context of the increasing effects of climate change. Finally, but most importantly, we highlight the topic of mycorrhizae as an eco-friendly strategy for sustainable agriculture and forestry.